ANALISIS PENGARUH RELIGIUSITAS DAN PENGETAHUAN TERHADAP MINAT MASYARAKAT UNTUK MENABUNG DI BANK SYARIAH (Studi Kasus Masyarakat Panyabungan Kota) - SITI SOPUROH; Ian Alfian; Paisal Rahmat (EKSYA : Jurnal Ekonomi Syariah, 2024)
This research aims to analyze the influence of religiosity and product knowledge on people's interest in saving at Islamic banks in Panyabungan City. The data collection method used a questionnaire with a total of 100 respondents, while the data analysis method used was multiple linear analysis using SPSS version 21. Partial t-test results of this study show that religiosity has a significant effect on the interest in saving of the people of Panyabungan City with a significant value of 0.000 < 0,005 and product knowledge has a significant effect. on interest in saving with a significance value of 0.000 < 0,005. The results of the coefficient of determination obtained R2 of 0.709 or 70.9%, which means that people's interest in saving is influenced by religiosity and product knowledge. Meanwhile, the remaining 29.1% is influenced or explained by other variables that are not included in this research. Keywords: Religiosity, Knowledge, and Interest in Saving